Distribution and severity of rubber diseases in Malaysia. - Shamsul Kamar A S (IRRDB symposium on diseases of Hevea Cochin, India, 21-22 November 1994, 1994)
The Rubber Research Institute of Malaysia conducts a survey every two years to monitor disease distribution and severity. About 200 selected sites, representing different rubber growing areas, have been visited for this purpose. The clones and fields chosen were based on clonal susceptibility and locality. In the 1993 survey, Oidium Secondary Leaf Fall (SLF) was prevalent and was severe throughout the country. The other two major leaf diseases, Collectotrichum Secondary Leaf Fall (SLF) and Corynespora Leaf Fall (LF) caused light to moderate infection. However, Corynespora LF was severe in several sites in Johore. Exotic or new diseases were not detected in the survey. Data collected from the survey are used to delineate disease epidemic areas. The severity of infection of popularly planted clones was also recorded. Changes in disease pattern and severity are discussed.
Keywords: Clonal susceptibility; Colletotrichum; Corynespora; Disease severity; Malaysia; Oidium; Rubber diseases; Secondary leaf fall (SLF)